Coastal Communities Environmental Concerns Based on Civic Culture - Mariatul Kiptiah; Wahyu; Rabiatul Adawiah; Muhammad Elmy (International Journal of Science and Society, 2022)
In the context of coastal communities, the need for civic culture arise as an idea related to the moral or ethical identity of citizens in their relationship with the environment. Community participation in protecting the environment is extremely important, the study of cultural issues in Indonesia cannot be separated from the knowledge of national values. Environmental concerns of coastal residents in Tanah Laut Regency, South Kalimantan, Indonesia in relation to their integrated coastal natural management, including the control, benefits and functions of utilizing coastal natural resources. Utilization of coastal resources includes biological resources. Not only the utilization of biological natural resources, but also ecological services of the coastal natural environment, building intelligence and artificial resources, in terms of managing coastal area resources that bring numerous benefits to human life and other living creatures. Coastal communities, not only makes a living by being fishermen, but also as traders and farmers, because of the biographical nature of the people who also live in the highlands. They can be called agrarian communities or local farmers. Likewise with the topography and the elevation map of the study area, it increase environmental awareness amongst coastal communities and enable them to improve the welfare of the community.